Recantation After Disclosure of Child Sexual Abuse: The Perspective of Professionals - Dias Baía, Pedro Augusto; Alberto, Isabel Maria Marques; Dell’Aglio, Débora Dalbosco (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The recantation after disclosure of child sexual abuse (CSA) configures situations in which potential victims deny their previous reports. This study aimed to identify, from the perspective of professionals, the risk and protective factors associated with recantation. Individual interviews were conducted with 23 professionals, social workers, tutelary counselors, magistrates, pedagogues, and psychologists, from Brazil and Portugal. From the thematic analysis carried out, six themes related to the risk factors emerged: “Conditions Related to the Child”, “Proximity between Victim and Aggressor”, “Disclosure in the Informal Context”, “Family System”, “Community Pressures” and “CSA Assistance Network”. Two themes related to protection factors emerged: “Service Procedures” and “Institutional Strategies”. The themes found denote the importance of an ecological and multidisciplinary approach to retraction. The implications of the results for the field of assessment of the risk of recantation and the responses to be provided by judicial and non-judicial entities are discussed.